PROBLEMS OF TRAINING PHYSICAL EDUCATION SPECIALISTS IN HIGHER EDUCATIONAL INSTITUTIONS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article considers the professional competence of a university teacher as interconnected blocks comprising pedagogical activity, pedagogical communication, the teacher’s personality, students' training and development levels. The structure of activity is described through diagnostic, design, constructive, organizational, and communicative skills.